The Application of Waqf in Kitabisa Platform: A Living Qur'an Study - Muhammad Iqbal Fatoni; Aunur Rofiq; Ahmad Djalaludin (Fakultas Agama Islam Universitas Islam Al-Azhar, 2025)
Waqf is a sunnah order in Islamic law that lasts until now, waqf has been transformed into a digital platform. then the kitabisa platform emerged as a waqf manager from the community because Islamic law orders must be in accordance with the principles of the Qur'an. This research uses a qualitative method with a living qur'an approach to find out the principles and practices of al qur'an in the kitabisa platform. Data were collected through literature studies on waqf and the kitabisa platform, as well as websites and annual reports owned by the kitabisa platform. This research is only limited to the kitabisa application and its waqf programs. This research shows that the kitabisa platform is in accordance with the principles of the Qur'an regarding waqf because it uses the appropriate Qur'anic arguments and also gives the impact of waqf to the wider community. For example, to the poor, orphans and the environment.